Pengaruh Pemberdayaan terhadap Self-Efficacy pada Pasien Kanker Payudara: Systematic Review - Purnomo, Purnomo; Nuraini, Tuti; Putri, Yossie Susanti Eka; Maria, Riri (Faletehan Health Journal, 2025)
Breast cancer is the second most prevalent type of cancer and one of the leading causes of mortality. Efforts to reduce mortality rates can be achieved by empowering patients to manage symptoms caused by cancer and the side effects of treatment therapies. This study aimed to evaluate the effectiveness of empowerment education in increasing self-efficacy in breast cancer patients. The study employed a systematic review of eight articles sourced from various databases, including ProQuest, SpringerLink, ScienceDirect, Sage Journal, Google Scholar, and PubMed. A total of 8,693 articles were retrieved from seven databases. After screening based on inclusion criteria, 638 articles were deemed eligible. Based on the selection of titles, abstracts, and full texts, 22 articles were chosen, and after duplicate elimination, 10 articles were analyzed using the Joanna Briggs Institute (JBI) quality assessment tool. The analysis results indicated that the empowerment approach is effective in improving self-efficacy and quality of life in breast cancer patients. By utilizing empowerment education, healthcare professionals can provide holistic support to patients, improve therapeutic outcomes, and reduce breast cancer mortality rates. This study recommended the integration of empowerment education as an essential component of breast cancer management in various healthcare facilities.